Colonoscopic study of 50 patients with colonic tuberculosis. Issue 3 (March 1992) - Shah, S; Thomas, V; Mathan, M; Chacko, A; Chandy, G; Ramakrishna, B S; Rolston, D D
Abstract : Fifty patients with colonic tuberculosis are reported in whom a colonoscopic diagnosis confirmed by histological examination was possible in 40. Bacteriological studies did not increase the diagnostic yield. Abdominal pain was the most common symptom (90%) and an abdominal mass the most common abnormal physical finding (58%). A nodular mucosa with areas of ulceration was the usual colonoscopic finding. Ileocaecal disease was found in 16, ileocaecal and contiguous ascending colon disease in 14, segmental colonic tuberculosis in 13, ileocaecal disease and non-confluent involvement of another part of the colon in five, and pancolitis in two patients. This report emphasises that colonoscopy is a useful procedure for diagnosing colonic tuberculosis and that segmental colonic tuberculosis is not uncommon.